Intraoperative povidone-iodine irrigation for infection prevention - Goswami, Karan (Arthroplast Today, 2019)
Although prevention of infection following arthroplasty requires a multifaceted approach, the use of intraoperative irrigation is an important component of any protocol. Recent clinical practice guidelines from the Centers for Disease Control, World Health Organization, and International Consensus Meeting on Musculoskeletal Infection advocate the use of a dilute povidone-iodine solution prior to wound closure. Our experience suggests that this practice is safe, inexpensive, and easily implemented. The present article describes our institutional irrigation protocol and reviews the current literature regarding povidone-iodine solutions.